Epigenetic repurposing of carbohydrate metabolic inhibitors for insulin resistance: targeting DNMT1 and HDAC3 for β-cell restoration - Iqbal, Muhammad Javid; Salazar, Luis A. (Frontiers in Epigenetics and Epigenomics, 2025)
Insulin resistance, a global metabolic crisis affecting a substantial portion of the world’s population, involves complex metabolic-epigenetic crosstalk that current therapies fail to address. DNA methyltransferase 1 (DNMT1) and histone deacetylase 3 (HDAC3) progressively silence insulin signaling genes, creating a self-perpetuating cycle of metabolic dysfunction. We present a hypothetical cross-target repurposing strategy leveraging established α-amylase and α-glucosidase inhibitors as potential epigenetic modulators. Through systematic computational screening of 100 natural metabolic enzyme inhibitors against DNMT1 and HDAC3 crystal structures (PBD ID: 3PTA, 4A69), we identified ten dual-target candidates with binding affinities ranging from −8.1 to −10.2 kcal/mol. Kotalanol emerged as the lead compound, demonstrating strong binding to both HDAC3 (−9.8 kcal/mol) and DNMT1 (−10.2 kcal/mol). Molecular docking revealed that polyphenolic metabolic inhibitors share structural features enabling interaction with epigenetic enzyme active sites, particularly zinc-binding motifs and aromatic pockets. ADMET profiling confirmed favorable pharmacokinetic properties for the top candidates. Clinically validated compounds including berberine, curcumin, and EGCG provide proof-of-concept for dual metabolic-epigenetic activity. This repurposing approach offers significant advantages: utilizing compounds with established safety profiles, addressing multiple pathogenic mechanisms simultaneously, and accelerating therapeutic development. By targeting both immediate glucose control and long-term epigenetic preservation, these dual-action compounds could transform diabetes management from symptomatic treatment to mechanistic intervention, potentially reversing insulin resistance progression rather than merely managing hyperglycemia.